2021
DOI: 10.2478/johh-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Local scour around a bridge pier under ice-jammed flow condition – an experimental study

Abstract: The appearance of an ice jam in a river crucially distorts local hydrodynamic conditions including water level, flow velocity, riverbed form and local scour processes. Laboratory experiments are used for the first time here to study ice-induced scour processes near a bridge pier. Results show that with an ice sheet cover the scour hole depth around a bridge is increased by about 10% compared to under equivalent open flow conditions. More dramatically, ice-jammed flows induce both greater scour depths and scour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Figure 18 shows the comparison of scour hole slope between two scouring states in the scouring equilibrium stage, both of them have relatively steep scour holes along the front of the pier, while the slope at the end of the pier is gentle and the tail area shows a dune accumulation pa ern, in which under the clear-water scouring condition, the gradient of the flush pit of the front pier undercut by the water flow (straight line A1B1 inclination in the diagram) is about 29°, and the gradient of the flush pit on the pier side (straight line C1D1 inclination in the figure) is about 30°. The gradient of the flush pit of the front pier undercut by the water flow (straight line A2B2 inclination in the figure) is about 23°, and the gradient of the flush pit on the pier side (straight line C2D2 inclination in the figure) is 24°; by comparison, it was found that the slope is smaller than the repose angle of the submerged sediment of 32°, indicating that the quasi-equilibrium scour hole has reached a stable state [45].…”
Section: Scale Of Scouring Hole Side Wallsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 18 shows the comparison of scour hole slope between two scouring states in the scouring equilibrium stage, both of them have relatively steep scour holes along the front of the pier, while the slope at the end of the pier is gentle and the tail area shows a dune accumulation pa ern, in which under the clear-water scouring condition, the gradient of the flush pit of the front pier undercut by the water flow (straight line A1B1 inclination in the diagram) is about 29°, and the gradient of the flush pit on the pier side (straight line C1D1 inclination in the figure) is about 30°. The gradient of the flush pit of the front pier undercut by the water flow (straight line A2B2 inclination in the figure) is about 23°, and the gradient of the flush pit on the pier side (straight line C2D2 inclination in the figure) is 24°; by comparison, it was found that the slope is smaller than the repose angle of the submerged sediment of 32°, indicating that the quasi-equilibrium scour hole has reached a stable state [45].…”
Section: Scale Of Scouring Hole Side Wallsmentioning
confidence: 94%
“…Figure 18 shows the comparison of scour hole slope between two scouring states in the scouring equilibrium stage, both of them have relatively steep scour holes along the front of the pier, while the slope at the end of the pier is gentle and the tail area shows a dune accumulation pattern, in which under the clear-water scouring condition, the gradient of the flush pit of the front pier undercut by the water flow (straight line ; by comparison, it was found that the slope is smaller than the repose angle of the submerged sediment of 32 • , indicating that the quasi-equilibrium scour hole has reached a stable state [45].…”
Section: Scale Of Scouring Hole Side Wallsmentioning
confidence: 97%
“…Wang et al [5] pointed out that the development of an ice jam can be divided into following three stages: the initial development of an ice jam from downstream toward upstream of a channel (stage 1); the formation of an initial ice jam along the entire channel (stage 2); and the thickening process of the initial ice jam accompanied by the migration process of ice waves (stage 3). During the third stage, the incoming ice particles from the upstream section will be entrained by flowing water and submerged and accumulated under the initial ice jam and gradually transport downstream.…”
Section: Interaction Of Local Scour and Ice Wave Migrationmentioning
confidence: 99%
“…When a bridge pier is present in a river, the pier affects the transport capacity of ice particles and floes, the thickness of ice jams, and the water level around it. In the meantime, the appearance of an ice jam results in intense local scour around piers [5]. The presence of scour holes around bridge piers changes the flow structure and influences the migration of the ice wave process around bridge piers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation